The Effects of a Micro Hole in the First Convolution of a Bellows with Positive Rotation Angle on the Stress Behaviour - KIM, Jinbong (Engineering Transactions, 2016)
A bellows is widely used as the element of an expansion joint in various piping system. It suffers from axial movement, lateral deflection and angular rotation caused by vibration, thermal expansion, etc. A bellows absorbs regular or irregular expansion and contraction. Although a number of studies on the behaviour of these movements for a non-defective bellows have been carried out, studies on this behaviour for a bellows with defect are very few. This paper studies the effects of a micro-defect on the stress behaviour of the bellows. While the distributions of micro-defect are various, the analysis is performed for the case, in which the defect is on the first convolution what is expected to incur the maximum stress. The von Mises stress distribution for the bellows and around the hole is obtained. In addition, the relationship between lateral deflection and positive rotation angle for the von Mises stress for the bellows with microhole is also obtained.